Intravascular Ultrasound Detection of Vasa Vasorum Blood Flow Distribution in Coronary Artery Vessel Wall - Moritz, Regina (2012)
There is an increased body of evidence to suggest that the vasa vasorum play a major role in the progression and complications of vulnerable plaque leading to acute coronary syndrome. We propose the concept that detecting changes in the flow in the vascular wall by IVUS signals can quantify the presence of vasa vasorum. The results obtained in porcine model of atherosclerosis suggest that IVUS-based estimates of blood flow in the arterial wall can be used in vivo in a clinical research setting to establish the density of vasa vasorum as an indicator of plaque vulnerability.